Monetary Policy Transmission in Mauritius Using a VAR Analysis - Tsangarides, Charalambos (Washington, D.C. : International Monetary Fund, 2010)
Applying commonly used vector autoregression (VAR) techniques, this paper investigates the transmission mechanism of monetary policy on output and prices for Mauritius, using data for 1999-2009. The results show that (i) an unexpected monetary policy tightening-an increase in the Bank of Mauritius policy interest rate-leads to a decline in prices and output but the effect on output is weaker; (ii) an unexpected decrease in the money supply or an unexpected increase in the nominal effective exchange rate result in a decrease in prices; and (iii) variations of the policy variables account for small a percentage of the fluctuations in output and prices. Taken together, these results suggest a rather weak monetary policy transmission mechanism. Finally, we find some differences in the transmission mechanism depending on whether core or headline consumer price index is used in the estimations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet